KINERJA PEMERINTAH KOTA DALAM MENGATASI PERSAMPAHAN DI MAKASSAR - Kamaruddin Tone (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
This study aims to determine the factors that influence in dealing with waste in the city of Makassar, this study used phenomenological approach and classified as qualitative research. The results showed that the waste problem is still on the agenda of homework that has not been able to overcome the maximum to date, this gives an indication that there is no synergy between the leadership of stakeholders, employees and the community in order to jointly tackle the waste problem, so the government needs to involve the community as a subject development in addressing the waste problem in the city of Makassar.